UJI PENDAHULUAN EFEKTIVITAS BIOINSEKTISIDA AKAR TUBA TERHADAP HAMA Oxya chinensis PADA SKALA LABORATORIUM - Danie Indra Yama; Jojon Soesatrijo; Rusnadi Santiko (Bioscientist : Jurnal Ilmiah Biologi, 2019)
The aim of this research is to knowtime of death, mortality and changes in behavior of Oxya chinensis in the treatment of botanical insecticides root of the tuba. The research was conducted at Laboratory Citra Widya Edukasi Palm Oil Polytechnic in Bekasi, the experimental design was the Completely Randomized Design, the treatment consisted of A0 = deltamethrin 0.3 cc/100 ml, A1 = tuba root extract 3g/100ml, A2 = tuba root extract 4g/100ml , A3 = tuba root extract 5g/100ml. Each treatment was repeated three times and each replication contained of 3 samples. Data were analyzed using variance with 5% level, if there is a real effect then tested further with the test of the Least Significance Different. Making extracts by means of tuba roots chopped until smooth, mixed with 100 ml of water, saved for 3 days, then filtered and taken water and the application is sprayed. Pest control using chemical insecticides is more effective than botanical insecticides root of the tubabut 4g/100ml botanical insecticides toba root are also potentially in Oxya chinensis death at 39,51 minutes after the application. The application of chemical and botanical insecticides made from tubaroots causes Oxya chinensis to decrease activity than dies.